2014
DOI: 10.3748/wjg.v20.i30.10440
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin knockdown suppresses the growth and angiogenesis of colon cancer cells

Abstract: Knockdown of OPN gene expression suppresses colon cancer cell growth, adherence, invasion, and expression of angiogenic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
2
34
1
Order By: Relevance
“…Furthermore, OPN is a well known gene involved in the regulation of proliferation, migration, and invasion of OSCC cells (49). Our results showed that miR-125a-mediated targeting of ESRRA indeed regulates the levels of WNT11 and OPN (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, OPN is a well known gene involved in the regulation of proliferation, migration, and invasion of OSCC cells (49). Our results showed that miR-125a-mediated targeting of ESRRA indeed regulates the levels of WNT11 and OPN (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, Lam et al (47) have shown that targeted inhibition of ESRRA inhibits the expression of SNAI1 (Snail family zinc finger 1) and in turn attenuates epithelial to mesenchymal transition in ovarian cancer cells. The mechanisms underlying these effects can be attributed to the ESRRA-driven regulation of several genes involved in cancer progression and development such as WNT11, CCNE1, OPN, and OPG, which are the crucial genes involved in increasing the proliferative and migratory capacity of cells (17,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Areas of decreased incidence include South America, Africa and Asia. The morbidity and mortality of colorectal cancer differs between areas of increased and decreased incidence (5).…”
Section: Introductionmentioning
confidence: 99%
“…OPN and VEGF contribute to tumor progression [8,12,19,20,62,[99][100][101][102] and angiogenesis [11,12,16,21,28,37,93,99,100,[103][104][105][106][107][108]. The inhibition of OPN may reduce VEGF levels and suppress tumor progression [85,[109][110][111][112].…”
Section: Cancermentioning
confidence: 99%